Foliar application of calcium and kinetin on soybean at reproductive stage - Fioreze, Samuel Luiz; Carneiro, João Paulo Costa; Pinto, Daniela Dias; Rodrigues, João Domingos (Taylor & Francis, 2017)
We characterized the pollination and fecundation times in soybean flowers and evaluated the effects of kinetin and calcium applications on physiological and productive traits of soybean plants during the reproductive stage. The anatomical study of flowers of eight soybean cultivars showed that fecundation occurred in closed flowers with visible petals, which presented embryo in the first cell divisions. These results indicate that fertilizers and growth regulation applications should be performed before flower opening, which is different from the current recommendation. Foliar applications of kinetin and calcium between the floral bud and full flowering stages did not affect carbon dioxide (CO2) assimilation, yield components and final yield. The results obtained in this research showed the lack of viability of foliar application of calcium and kinetin in order to increase pod set and number of seeds per plant in soybean crop.
Keywords: fecundation; flowers; glycine max; pollination; yield